2018
DOI: 10.3390/coatings8030099
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Ultraviolet-Curing Kinetics of Ultraviolet-Polymerized Oligomers Cured Using Poly (Ethylene Glycol) Dimethacrylate

Abstract: Ultraviolet (UV)-curable oligomers are increasingly being used in various industries because they can be applied rapidly and have excellent physical properties. Ultraviolet polymerization is used for manufacturing such oligomers. Reactive diluents, which are employed during the secondary curing of UV-curable oligomers, can help elucidate the curing behaviors of these oligomers. In this study, poly (ethylene glycol) dimethacrylate (PEGDMA) was used as the reactive diluent for UV-curable oligomers. Photodifferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…To better predict the lens profile, we need to incorporate the curing kinetics of the lens material in the numerical model. We also need to measure shrinkage using photo-differential scanning calorimetry, and measure the curing reaction heat using a differential scanning calorimeter and UV irradiation unit in future experiments [56][57][58]. The research group will study the effects of material shrinkage and curing reaction heat on lens shape in the numerical model.…”
Section: Future Workmentioning
confidence: 99%
“…To better predict the lens profile, we need to incorporate the curing kinetics of the lens material in the numerical model. We also need to measure shrinkage using photo-differential scanning calorimetry, and measure the curing reaction heat using a differential scanning calorimeter and UV irradiation unit in future experiments [56][57][58]. The research group will study the effects of material shrinkage and curing reaction heat on lens shape in the numerical model.…”
Section: Future Workmentioning
confidence: 99%
“…Previous studies have already shown many alternative approaches [8,13,14] and nano-imprint lithography (NIL) has proved to be more appropriate for processing the large-area surface texture [15][16][17][18][19][20]. Meanwhile, wet etching of absorbing materials (such as silicon) is widely used in the fabrication of the micro-pyramid structure by combining with the NIL technique [15,21]. Based on the better AR property of the micro-pyramid, a method to fabricate an optical multifunction structure was proposed by Päivänranta et al [22] by means of wet etching, nano-imprint lithography (NIL), and reactive ion etching (RIE).…”
Section: Introductionmentioning
confidence: 99%